Predictors of the highest long-term care expenditures in Japan - Kashiwagi Masayo; Tamiya Nanako; Olivares-Tirado Pedro; Kashiwagi Kimikazu (BMC, 2011)
Abstract Background In Japan, as the number of elderly covered by the Long-term Care Insurance (LTCI) system has increased, demand for long-term care services has increased substantially and consequently growing expenditures are threatening the sustainability of the system. Understanding the predictive factors associated with long-term care expenditures among the elderly would be useful in developing future strategies to ensure the sustainability of the system. We report a set of predictors of the highest long-term care expenditures in a cohort of elderly persons who received consecutive long-term care services during a year in a Japanese city. Methods Data were obtained from databases of the LTC insurer of City A in Japan. Binary logistic regression was used to examine the predictors of the highest long-term care expenditures. We used a simplified model that focused on the effects of disability status and type of services used, while controlling for several relevant factors. Goodness of fit, a multicollinearity test, and logistic regression diagnostics were carried out for the final model. Results The study cohort consisted of 862 current users of LTCI system in city A. After controlling for gender and income, age, increased utilization rate of benefits, decline in functional status, higher care needs level and institutional care were found to be associated with the highest LTCI expenditures. An increased utilization rate of benefits (OR = 24.2) was a strong main effect predictors of the high LTC expenditures. However, a significant interaction between institutional care and high care need level was found, providing evidence of the combined effect of the two covariates. Conclusions Beyond to confirm that disability status of elderly persons is the main factor driving the demand of LTC services and consequently the expenditures, we showed that changes in utilization rate of benefits -a specific insurance factor- and the use of institutional care conditional on the high care level, were strongest predictors of the highest LTC expenditures. These findings could become crucial for tracking policies aimed at ensuring financial sustainability of LTCI from a public insurer perspective in Japan.